Claw-Waving Behavior by Male UCA Lactea (Brachyura, Ocypodidae) in Vegetated and Un-Vegetated Habitats. Issue 2 (1st March 2015) - Sakagami, Maki; Miyajima, Aya; Wada, Keiji; Kamada, Mahito
Abstract: We compare the waving activity of male Uca lactea (De Haan, 1835 ) between vegetated and open, un-vegetated areas during the breeding season in the Yoshinogawa River Estuary, western Japan. Males that lived in open, un-vegetated areas invest more time in courtship waving than do males living in vegetated areas. This suggests that the waving activity of male U. lactea is depressed by the presence of vegetation. The proportion of surface active males that produce courtship waving and the waving intensity by individual males showed temporal difference between the two habitats: in the open area, peak waving occurred in August; in the vegetated area, peak waving occurred in May and June. This temporal effect is discussed in the light of predation pressure.